Resource acquisition, entrepreneurial competence, and entrepreneurial growth performance of new farmers - Shimei Yang; Song Yu; Song Yu; Lianjun Li; Lianjun Li (Frontiers in Sustainable Food Systems)
IntroductionEntrepreneurial resources and abilities are pivotal factors influencing the success of new farmers’ ventures. Understanding how these elements drive entrepreneurial growth is of significant practical importance.MethodsGrounded in a framework system for entrepreneurial competence (comprising opportunity recognition/exploitation capabilities and operational/strategic management proficiencies), this study uses field data from 512 new farmers in Jiangxi, Henan, and Anhui provinces. Mediation and structural equation models are applied to assess the impact of resource acquisition on entrepreneurial growth and explore the mediating role of entrepreneurial ability.ResultsResource acquisition significantly bolsters entrepreneurial growth performance. Within entrepreneurial skills, both opportunity recognition and operational management capabilities mediate the relationship between human, social, material resources and growth performance (effect sizes: 0.134, 0.286, 0.257, 0.105, 0.279, and 0.240). No mediation is observed for policy resources. The study identifies eight pathways: human, social, and material resources influence performance both directly and indirectly, while policy resources exert only a direct effect.DiscussionThese findings underscore the imperative to enhance new farmers’ accessibility to entrepreneurial resources, augment their capabilities (particularly opportunity recognition and operational management), reinforce policy support, and cultivate sustainable development of their entrepreneurial endeavors.